2021
DOI: 10.1007/s11666-020-01149-9
|View full text |Cite
|
Sign up to set email alerts
|

Size Effects of Brittle Particles in Aerosol Deposition—Molecular Dynamics Simulation

Abstract: Up to now, the role of particle sizes on the impact behavior of ceramic particles in aerosol deposition not yet fully understood. Hence, with the aim to supply a more general understanding, modeling series of low strain rate compression and high-speed impact were performed by molecular dynamics on single-crystalline particles in sizes of 10-300 nm that are tuned to match mechanical properties of TiO2-anatase. The modeling results reveal that particles with original diameter of 25-75 nm exhibit three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In fact, the stress calibration data provided by Sakshita et al [86] applies a maximum stress of 60 MPa to BaTiO 3 corresponding to a shift to 519 cm -1 , well exceeded by the as-processed film., i.e., 522 cm -1 . This is a strong indication that the as-processed film is deformed by the impact loading during the AD-process resulting in a lattice distortion [20,56,71,90]. During thermal treatment, as can be seen in Fig.…”
Section: In Situ Temperature-dependent Structural Investigationsmentioning
confidence: 82%
“…In fact, the stress calibration data provided by Sakshita et al [86] applies a maximum stress of 60 MPa to BaTiO 3 corresponding to a shift to 519 cm -1 , well exceeded by the as-processed film., i.e., 522 cm -1 . This is a strong indication that the as-processed film is deformed by the impact loading during the AD-process resulting in a lattice distortion [20,56,71,90]. During thermal treatment, as can be seen in Fig.…”
Section: In Situ Temperature-dependent Structural Investigationsmentioning
confidence: 82%
“…The test was used to adjust the ε parameter for finally reaching a compressive strength of 11.11 GPa in compression test simulation, comparable to the experimental data that are available from literature for TiO 2 -anatase nanoparticles within a diameter range of 30-40 nm [2,43]. Details of compression test simulation and its results can be found in our previous study [41].…”
Section: Compression Test Simulationsmentioning
confidence: 74%
“…3. In addition, extended MD simulations showed that the velocity regime for rebounding is not size dependent [41]. For the present material description of TiO 2 -anatase, the maximum rebounding velocity, here defined as threshold velocity, v threshold , is determined to 400 m/s for a range of particle diameters from 25 to 300 nm [41].…”
Section: Analytical Modelsmentioning
confidence: 88%
See 1 more Smart Citation
“…By experiments and modelling, most established descriptions associate bonding and layer formation in Aerosol Deposition with (dynamic) particle fragmentation into nanocrystalline microstructures (Ref 19,20,28). Another approach was followed by Daneshian et al by using molecular dynamic (MD) simulations (Ref 40,41). For nanoparticle impact, their computations distinguish regimes of (i) rebound (ii) deformation and bonding and (iii) particle fracture, whereas only deformation associated effects are defined to contribute to layer formation.…”
Section: Discussionmentioning
confidence: 99%